Differences in Tear Film Biochemistry of Symptomatic and Asymptomatic Lens Wearers. Issue 9 (September 2017) - Masoudi, Simin; Stapleton, Fiona J.; Willcox, Mark D. P.
Abstract : SIGNIFICANCE: The concentration of selected proteins and inflammatory mediators in tears of symptomatic and asymptomatic contact lens wearers were quantified. The level of leukotriene B4 was higher in the symptomatic group. This may suggest that inflammation can be the cause of discomfort sensation at the end of day. PURPOSE: The present study aims to quantify the concentration of selected tear lipids and proteins in symptomatic and asymptomatic contact lens wearers. METHODS: Unstimulated evening tears were collected using glass capillary tubes from 45 healthy, adapted contact lens wearers. Twenty-two had self-described symptoms of dryness and discomfort with contact lenses and 23 were asymptomatic. Tear proteins were assayed using selected reaction monitoring mass spectrometry. Enzyme immunoassay kits were used to measure prostaglandins, leukotriene B4, and cysteinyl leukotrienes. Ocular comfort was rated on a scale of 1 to 100 at the time of tear collection. RESULTS: The average evening comfort level was above 70 for the asymptomatic (83.96 ± 9.51, mean ± SE) and equal or below 70 for the symptomatic group (57.28 ± 12.38) ( P < .001). LTB4 was significantly higher in symptomatic than asymptomatic contact lens wearers (0.32 ± 0.06 ng/μL vs. 0.17 ± 0.04 ng/μL, respectively; P = .03). Lysozyme was slightly but not significantly lower in symptomatic subjects (symptomatic 0.58 ± 0.10 mg/mL vs. asymptomatic 1.73 ± 0.46 mg/mL; P = .10). The levels of lactoferrin, lipocalin 1, proline-rich 4, prolactin-induced protein, prostaglandins, and cysteinyl leukotrienes were unchanged ( P > .1) between symptomatic and asymptomatic subjects. CONCLUSIONS: The LTB4 concentration was significantly higher in symptomatic contact lens wearers compared to the asymptomatic group, and this may partly mediate the discomfort response during lens wear in the symptomatic lens wearers. No other differences were found in the level of tear factors of interest between the two groups.